Environmental Concerns In Oil Waste Processing - Ruziev I.Kh; Mirzakobilov B.Yu; Bazarbaev A. A; Shomurodova S.Sh (Zien Journals, 2025)
This paper analyzes the impact of oil and petroleum products on the ecosystem, addresses issues of soil pollution by petroleum products, and examines emergency situations involving the release or threat of release of hazardous chemical substances (HCS) due to explosions that cause the destruction of process networks and engineering structures. Furthermore, it presents challenges aimed at minimizing negative consequences and the rational use of natural resources in modern conditions
Keywords: Environmental pollution; oil refining; emissions of harmful substances